Pemetaan Kerawanan Tanah Longsor Berbasis Tujuh Karakteristik Geospasial di Kabupaten Nganjuk - Titisari Haruming Tyas; Ahmad Fatkul Fikri; Gita Yulianti Suwandi (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Hydrometeorological disasters have been the most dominant type of disaster in Indonesia in recent years. In 2025, there were 2,017 recorded disaster events, with 99.25% categorized as hydrometeorological disasters, including a landslide in Nganjuk Regency that caused fatalities, economic losses, and psychological impacts. Nganjuk Regency is highly vulnerable to landslides due to its location, with part of its area situated in the Mount Wilis region, which possesses specific geospatial characteristics. This study aims to analyze the geospatial characteristics of landslide disaster risk areas in Nganjuk Regency. The research method employs a qualitative approach with an analytical-descriptive design combined with spatial analysis techniques based on a Geographic Information System (GIS). Secondary data in the form of shapefile data were analyzed using ArcGIS software. The results showed that there are five levels of landslide disaster vulnerability in Nganjuk Regency: 1) non-vulnerable class covering an area of 12,303.90 ha; 2) slightly vulnerable class covering an area of 82,153.74 ha; 3) moderately vulnerable class covering an area of 26,822.28 ha; 4) vulnerable class covering an area of 7,246.37 ha; and 5) highly vulnerable class covering an area of 28.46 ha located in the Mount Wilis area. Abstrak. Bencana hidrometeorologi merupakan jenis bencana yang paling dominan terjadi di Indonesia dalam beberapa tahun terakhir. Pada tahun 2025, tercatat 2017 kejadian bencana dengan 99,25 kejadian merupakan bencana hidrometeorologi, termasuk tanah longsor di Kabupaten Nganjuk yang mengakibatkan korban jiwa, kerugian ekonomi, dan dampak psikologis. Kabupaten Nganjuk memiliki kerentanan tinggi terhadap tanah longsor karena sebagian wilayahnya berada di kawasan Gunung Wilis yang memiliki karakteristik geospasial tertentu. Penelitian ini bertujuan untuk menganalisis karakteristik geospasial wilayah risiko bencana tanah longsor di Kabupaten Nganjuk. Metode penelitian menggunakan pendekatan kualitatif dengan desain deskriptif-analitis yang dikombinasi dengan teknik analisis spasial berbasis Sistem Informasi Geospasial (SIG). Data penelitian menggunakan data sekunder berupa data shapefile yang dianalisis menggunakan software ArcGIS. Hasil penelitian menunjukkan terdapat lima kelas kerawanan bencana tanah longsor di Kabupaten Nganjuk: 1) kelas tidak rawan seluas 12.303,90 ha; 2) kelas sedikit rawan seluas 82.153,74 ha; 3) kelas rawan sedang seluas 26.822,28 ha; 4) kelas rawan seluas 7.246,37 ha; dan 5) kelas sangat rawan seluas 28,46 ha berada di daerah Gunung Wilis.